2001
DOI: 10.1007/s11664-001-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen in AlGaAs-based laser structures with Al-Free active region on device properties

Abstract: AlGaAs-based lasers with GaAsP active regions for emission wavelengths near 730 nm and 800 nm were studied. Trimethyl aluminum sources with different levels of oxygen concentration were used for the deposition of the laser structures. The laser data show that the oxygen level in the AlGaAs wave guides is very critical for the performance of the 730 nm devices, even for the use of an Alfree active region, while its influence is weak for the 800 nm devices. Using the TMAl source leading to the lowest O-uptake in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The integration of epitaxial gratings for short wavelength GaAs-based lasers is challenging for two main reasons: (i) The high Al content in cladding and waveguide layers results in oxygen contamination at the interface between the first and second growth step, creating deep-level trap states which promote non-radiative recombination and hence degrade the laser performance [7,8]. Investigations on regrowth conditions to suppress the oxygen contamination include the heatup procedure and doping techniques and have been published elsewhere [9].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of epitaxial gratings for short wavelength GaAs-based lasers is challenging for two main reasons: (i) The high Al content in cladding and waveguide layers results in oxygen contamination at the interface between the first and second growth step, creating deep-level trap states which promote non-radiative recombination and hence degrade the laser performance [7,8]. Investigations on regrowth conditions to suppress the oxygen contamination include the heatup procedure and doping techniques and have been published elsewhere [9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Oxygen forms a deep recombination level in III-V semiconductors and can increase the threshold current and reduce photoluminescence efficiency, minority-carrier lifetimes, and device reliability even at levels below 10 17 cm À3 . [1][2][3][4] The incorporation of oxygen in the growing film is more pronounced when the film contains highly reactive constituents such as aluminum. Therefore, it is important to identify and control critical oxygen-containing impurities in both Group III organometallic and Group V hydride gas precursors, especially when growing epitaxial films such as AlInP and AlGaInP.…”
Section: Introductionmentioning
confidence: 99%
“…7 A number of studies have shown that methoxide impurities in trimethylaluminum and trimethylindium precursors can significantly influence the quality of epitaxial layers. [2][3][4][5] In addition, it is also necessary to minimize water vapor contamination that may be introduced into the MOCVD tool from the phosphine process gas. 1,6 Water vapor is one of the most difficult impurities to eliminate because of its ubiquity and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of oxygenated impurities such as moisture must be minimized, particularly for the manufacture of high brightness opto-electronic devices. These impurities are incorporated into Alcontaining epilayers and can markedly affect properties such as photoluminescence [6,7]. In this work, the performance of a SAGE arsine source and delivery system has been tested and compared against an HP reference source for MOCVD.…”
Section: Introductionmentioning
confidence: 99%